Initial Stage of Formation of Spontaneous Invasive Populations of Garden Lupine (Lupinus polyphyllus Lindl.) at the Northern Limit of Its Secondary Distribution Range in the Veps Forest Nature Park - Maria A. Galkina; Yulija K. Vinogradova; Viktoria N. Zelenkova; Natalia V. Vasilyeva; Ekaterina V. Tkacheva; Olga V. Shelepova (Agronomy, 2022)
A weed plant of the species Lupinus polyphyllus was found in settlements located on the territory of the natural park “Vepssky forest” of the Leningrad region. The plant is known as a transforming species in the southern regions of Russia. The distribution of L. polyphyllus within the Vepsian forest occurs not due to the migration of the species to the north along transport routes, as one might assume, but due to flight from gardens and the formation of spontaneous invasive populations. The goal of the study was to identify the molecular and biochemical characteristics of garden lupine at the northern borders of its secondary range. To interpret the obtained data, the task of the study also included a comparison of intraspecific variability between the “old” invasive populations (in Finland and Central Russia, studied by us earlier) and the “new” naturalizing population of L. polyphyllus in the Vepsian forest. The search for L. polyphyllus localities in the territory of the Vepssky Les natural park was carried out by the route method with geobotanical descriptions of experimental sites (5 m × 5 m). DNA was isolated from eight herbarium specimens of L. polyphyllus (MHA, LE) and fifteen specimens collected in the territory of the natural park “Vepssky Les”. To reveal the internal structure and phylogenetic relationships in lupine populations, networks of nuclear and chloroplast haplotypes and cluster analysis (UPGMA) with the SplitsTree program were used. The total content of polyphenols and flavonoids in the leaves was determined spectrophotometrically. The low inter-locality variability of ITS indicates that the populations of L. polyphyllus in Central Russia and in the North of Russia (St. Petersburg and Vepsskaya Pushcha) have the same origin. Analysis of the chloroplast intergenic spacer (rpl32–trnL) indicates intrapopulation diversity and suggests the presence of microevolutionary processes near the northern limits of the secondary distribution range of L. polyphyllus. The high content of polyphenols and flavonoids in the leaves reveals the adaptive capabilities of lupine in the studied area. Evidence suggests that a neglected species may soon become invasive, as has already happened in other regions.